2020
DOI: 10.5603/mrj.a2020.0016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of pulsatility index

Abstract: Pulsatility index (PI) is defined as the difference between the peak systolic flow and minimum diastolic flow velocity, divided by the mean velocity recorded throughout the cardiac cycle. It is a non-invasive method of assessing vascular resistance with the use of Doppler ultrasonography. It was first introduced in 1974 by Gosling and King and is also known as the Gosling Index. PI as a method of examining macrocirculation has a variety of clinical applications. For instance, in diabetic patients, it has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…2 I , colored traces). Pulsatility indices, defined as the difference between the peak systolic flow and minimum diastolic flow velocity divided by the mean velocity throughout the cardiac cycle ( 34 ), were calculated for the same vessels with and without anesthesia (six arterioles from two mice and eight venules from four mice; Fig. 2 K ).…”
Section: Resultsmentioning
confidence: 99%
“…2 I , colored traces). Pulsatility indices, defined as the difference between the peak systolic flow and minimum diastolic flow velocity divided by the mean velocity throughout the cardiac cycle ( 34 ), were calculated for the same vessels with and without anesthesia (six arterioles from two mice and eight venules from four mice; Fig. 2 K ).…”
Section: Resultsmentioning
confidence: 99%
“…Although we hypothesized that ICA pulsatility index would be associated with cfPWV in the older adults, this association did not reach the threshold for significance. The ICAs have a larger diameter than the MCAs and basilar artery and previous research has demonstrated that increased arterial diameter influences pulsatility index ( 31 ). As such, we speculate that the ICAs may have higher elasticity than the MCAs and basilar artery, which may account for the slightly lower pulsatility index values in the ICA compared to the MCAs and basilar artery.…”
Section: Discussionmentioning
confidence: 99%
“…Increased arterial stiffness is a strong indicator of the increased risk of mortality and cardiovascular events [19,20,21]. The PI in diabetic patients may predict cerebrovascular complications, while in hypertensive individuals reflects chronicity of the disease [19][20][21].…”
Section: Discussionmentioning
confidence: 99%